2010
DOI: 10.1371/journal.pone.0011286
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Role for Syndecan Family Members in the Regulation of Whole-Body Energy Metabolism

Abstract: Syndecans are a family of type-I transmembrane proteins that are involved in cell-matrix adhesion, migration, neuronal development, and inflammation. Previous quantitative genetic studies pinpointed Drosophila Syndecan (dSdc) as a positional candidate gene affecting variation in fat storage between two Drosophila melanogaster strains. Here, we first used quantitative complementation tests with dSdc mutants to confirm that natural variation in this gene affects variability in Drosophila fat storage. Next, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 91 publications
8
53
1
Order By: Relevance
“…interactions and matrix-mediated cellular signaling cascades impacts the decline of age-dependent physiological performance and thereby life span (Goddeeris et al, 2003;Hansen et al, 2005;Wolfson et al, 2009;De Luca et al, 2010;De Luca et al, 2011;Wilson et al, 2013;Nishimura et al, 2014). Consistently, here we report that common genetic variants in the SDC4 gene affect human longevity.…”
Section: Growing Evidence From Model Systems and Humans Suggest Thatsupporting
confidence: 87%
See 3 more Smart Citations
“…interactions and matrix-mediated cellular signaling cascades impacts the decline of age-dependent physiological performance and thereby life span (Goddeeris et al, 2003;Hansen et al, 2005;Wolfson et al, 2009;De Luca et al, 2010;De Luca et al, 2011;Wilson et al, 2013;Nishimura et al, 2014). Consistently, here we report that common genetic variants in the SDC4 gene affect human longevity.…”
Section: Growing Evidence From Model Systems and Humans Suggest Thatsupporting
confidence: 87%
“…Furthermore, G allele carriers had higher levels of TG. This is particularly intriguing since we previously showed that American children (age 7 to 12 years)homozygous for the minor G-allele of rs1981429 had more intra-abdominal fat and less lean tissue mass (De Luca et al, 2010). Data on visceral fat were not available in the Italian cohort so we could not test for association between this trait and rs1981429.…”
Section: Growing Evidence From Model Systems and Humans Suggest Thatmentioning
confidence: 92%
See 2 more Smart Citations
“…deduced to be under separate control, because they are targeted by different genetic drivers and respond to different cues. So far, there are no direct data that describe insulator activity in Drosophila ; however, the metabolic phenotypes described for the syndecan Sdc1 Ϫ / Ϫ insulation-defective mouse model (described in the following paragraph) are remarkably coincident with Sdc mutant Drosophila ( 33 ). Evidence points toward dWAT having a simple insulator function, with the support of hair covering as a relatively newer evolutionary innovation for this group of cells.…”
Section: Downloaded Frommentioning
confidence: 99%